1979
DOI: 10.1042/bj1820727
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthesis by hepatocytes from diabetic rats

Abstract: Hepatocytes prepared from streptozotocin- and alloxan-diabetic rats starved for 24 h contain 0.5--2% wet wt. of glycogen. Glycogen synthesis in the hepatocytes from such rats, after prior depletion of the glycogen by glucagon injection, was studied. As distinct from cells from normal animals, there was no glycogen synthesis from glucose as sole substrate, even at concentrations of 60 mM. When supplied with glucose, a gluconeogenic precursor (lactate, dihydroxyacetone or fructose), and with glutamine there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
38
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 23 publications
10
38
0
Order By: Relevance
“…Because STZ causes selective destruction of β-cells of islets of Langerhans, resulting in a marked decrease in insulin levels, it is rational that glycogen levels in tissues (skeletal muscle and liver) decrease as the influx of glucose in the liver is inhibited in the absence of insulin and recovers on insulin treatment (Vats et al, 2004;Golden et al, 1979;Weber et al, 1966). Our results showed that BNRE supplementation to diabetic rats significantly elevated both muscle and hepatic glycogen contents (Table 5).…”
Section: Discussionsupporting
confidence: 53%
“…Because STZ causes selective destruction of β-cells of islets of Langerhans, resulting in a marked decrease in insulin levels, it is rational that glycogen levels in tissues (skeletal muscle and liver) decrease as the influx of glucose in the liver is inhibited in the absence of insulin and recovers on insulin treatment (Vats et al, 2004;Golden et al, 1979;Weber et al, 1966). Our results showed that BNRE supplementation to diabetic rats significantly elevated both muscle and hepatic glycogen contents (Table 5).…”
Section: Discussionsupporting
confidence: 53%
“…Most of these insulin effects have been small, however, and to our knowledge insulin has never been shown to cause a net accumulation of liver glycogen from glucose or any other substrate. This was certainly the case in the present study and in those described by Golden et al (30) and peripheral tissues. When the diet contained sucrose, fructose would provide an additional source of gluconeogenic carbon.…”
supporting
confidence: 47%
“…Glycogen is the primary intracellular storable form of glucose and its level in various tissues especially in liver and skeletal muscles indicates direct reflection of insulin activity since it regulates glycogen storage by stimulating glycogen synthase and inhibiting glycogen phosphorylase (Golden et al 1979). Because STZ causes destruction of β-cells of islets of Langerhans resulting in marked decrease in insulin levels, the glycogen content in tissues (liver and muscle) decrease as the invasion of glucose in the liver is inhibited in the absence of insulin (Weber et al 1966;Vats et al 2004).…”
Section: Discussionmentioning
confidence: 99%